Influencia del consorcio microbiano en la biosorción de cromo total de la etapa de curtido de curtiembre Inversiones Harod SAC - Rodriguez Yupanqui, Magda Rubi (2019)
ABSTRACT The effluent from the tanning process generates negative impacts on health and the environment because at this stage only 70% of the total chromium (Cr) used is used; whereby bioadsorption emerges as an alternative in the removal of heavy metals. In this regard, the objective of the present investigation was to evaluate the capacity of chromium removal in effluents from the tanning stage of the tannery Harold SAC tannery using as yeast sorbent of the genus Saccharomyces cerevisiae (S), Pichia guilliermondii (P) and the microbial consortium consisted of (S) + (P); These were isolated from agroindustrial waste. For the observation of yeast cells, an OLYMPUS brand binocular microscope, Mo.CX23LFS1, was used. The experimental procedure consisted of the use of 6 bioreactors of 250 ml conditioned with samples of effluent from the tanning stage, having the consortium (S + P) as sorbent, controlled at 0, 6, 12 and 24 hours. The samples were analyzed by the flame atomic absorption spectrophotometry technique using an INSTRUMENTS brand spectrophotometer. The results show that the yeast consortium has the total chromium removal capacity of 57% and 54% for initial concentrations of 50 and 100 ppm respectively. Likewise, the statistical evaluation with ANOVA allows us to affirm that there is no significant difference (p> 0.05) when using both concentrations, so it is advisable to use the highest concentration in the biosorption process of tanneries effluents.